Impact of a Portable Energy Efficiency Intelligence Power Socket (PEEiPS) for IoT Deployment - M.R. Mohd Roni; H.H. Hanafee; N.H. Mohd Yusoff (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2025)
In the rapidly evolving domain of smart technology and Internet of Things (IoT) integration, the imperative for portable and energy-efficient solutions has become increasingly critical. The Portable Energy Efficiency Intelligence Power Socket (PEEiPS) represents a groundbreaking innovation in addressing the pervasive issue of energy wastage resulting from human forgetfulness in turning off electrical appliances. By integrating the ESP8266 microcontroller with IoT capabilities and solar energy, PEEiPS offers a robust solution to combat energy wastage caused by the common problem of leaving electrical appliances on unnecessarily. The automated switching feature, driven by the HC-SR04 ultrasonic sensor can be set to ensure devices are active only when needed, effectively addressing energy inefficiencies. PEEiPS's reliance on solar power enhances its sustainability, offering an environmentally friendly alternative to traditional energy management systems. The results demonstrate that PEEiPS can achieve significant energy savings, reducing total energy consumption from 12,000 kWh per year to 11,654 kWh per year. This represents a 3.63% saving for devices with a 600W usage and a substantial 36.3% saving for devices with a 6000W usage. The mobile application facilitates convenient remote control and monitoring, fostering user engagement and improving energy management practices. PEEiPS presents a promising avenue for enhancing energy efficiency and promoting sustainable energy practices, ultimately mitigating environmental impact and reducing electricity costs in residential and commercial settings. The implications of these findings are significant, suggesting that PEEiPS has the potential to revolutionise energy management practices in IoT deployments. Moving forward, further research and development efforts could focus on refining PEEiPS's functionalities, scalability, and interoperability to maximize its commercial potential and applicability across various industries. Additionally, initiatives to raise awareness and promote the adoption of PEEiPS could be instrumental in driving widespread adoption and realizing its full impact on energy conservation efforts globally.